Duration of exclusive breastfeeding is associated with differences in infants’ brain responses to emotional body expressions - Krol, Kathleen M.; Rajhans, Purva; Missana, Manuela; Grossmann, Tobias (Frontiers in Behavioral Neuroscience, 2015)
Much research has recognized the general importance of maternal behavior in the early development and programming of the mammalian offspring’s brain. Exclusive breastfeeding duration, the amount of time in which breastfed meals are the only source of sustenance, plays a prominent role in promoting healthy brain and cognitive development in human children. However, surprisingly little is known about the influence of breastfeeding on social and emotional development in infancy. In the current study, we examined whether and how the duration of exclusive breastfeeding impacts the neural processing of emotional signals by measuring electro-cortical responses to body expressions in 8-month-old infants. Our analyses revealed that infants with high exclusive breastfeeding experience show a significantly greater neural sensitivity to happy body expressions than those with low exclusive breastfeeding experience. Moreover, regression analyses revealed that the neural bias toward happiness or fearfulness differs as a function of the duration of exclusive breastfeeding. Specifically, longer breastfeeding duration is associated with a happy bias, whereas shorter breastfeeding duration is associated with a fear bias. These findings suggest that breastfeeding experience can shape the way in which infants respond to emotional signals.